Effect of different nitrogen Sources Supplement on the final crude protein Yield from fermented Corn cob - Jabbar F. Al. maadhidi; Mustafa T. Al-Khatib; Shaimaa R. Farhan; Huda Fahim (Journal of Madenat Alelem University College, 2010)
Defferent nitrogen Sources (Urea,monoammonium phosphate (MAP),Compound Nitrogen Phosphate Fertilizer (NP) ,Ammonium Sulphate (NH4)2SO4 and phosphate urea)were used as supplements for growing yeast (Saccharomyces cerevisiae )on fermentation medium containing 10%crushed,processed corn cob and molasse as carbon source.Results revealed supplementation the medium with5% urea and 4% molasse gave the highest growth yield of yeast and increased the crude protein from2.4%(in the untreated corncob) to 22% after fermentation. The second nitrogen source effect was MAP+ammonium sulfate yealding 17%crude protein, while MAP+Urea yield 13.125%. The experiments were conducted in shaker incubator at 30cº,pH5,150rpm for 72hrs.